Implementasi Metode Dakwah Di Masjid Al-Hidayah Desa Tlogoretno Kecamatan Brondong Kabupaten Lamongan - Siti Kris Fitriana Wahyu Lestari (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
Da'wah is an activity to invite, call and broadcast information and teachings of the Islamic religion. In preaching, using correct and appropriate da'wah methods will be able to achieve success in da'wah activities. Because no matter how good or interesting the method or material provided, not using the right da'wah method will affect the success of the da'wah. Where the dawak must use the right method for each mad'u need. In developing and revitalizing the Al-Hidayah mosque in Tlogoretno Village, Brondong District, Lamongan Regency, this mosque has carried out and preserved several methods of preaching used to broadcast the Islamic religion. In its preaching method, the Al-Hidayah mosque uses the bil hal da'wah method, the verbal bil da'wah method, and the bil qalam da'wah method. This da'wah method is a da'wah method that can be accepted by both mad'u and the community so that da'wah activities at the al-Hidayah mosque can achieve success in preaching. However, apart from the supporting factors that can be successful in preaching at the Al-Hidayah mosque, there are also obstacles in carrying out this preaching. In this study, the research data used an approach from qualitative research methods with observations at the Al-Hidayah mosque in Tlogoretno Village, Brondong District, Lamongan Regency. The results of the research show that the da'wah method strategy is well accepted by mad'u or the community in Tlogoretno Village, Brondong District, Lamongan Regency. However, to further develop or revive the mosque, several activities are still needed that can be added to further advance or revive the mosque.